The Influence of Multi-Actor Collaboration between Universities on the Formulation of Waste Management Policies - Riska Sarofah; Sidik Firmadi; Hilal Ramdhani; M.Ananda Syahdani; Nadia Sabila Nurhaliza (Pencerah, 2026)
This study aims to examine the influence of university collaboration, particularly lecturer research within a multi-actor network, on the formulation of waste management policies in Tasikmalaya City. Despite the existence of Regional Regulation No. 7 of 2012 and Mayoral Regulation No. 22 of 2019, waste management remains suboptimal due to low community participation, limited facilities, weak inter-agency coordination, and budget constraints. This study employs a mixed-method approach, combining a quantitative survey of lecturers from seven universities with in-depth interviews and observations. Quantitative data were analyzed using simple linear regression, while qualitative data were examined through triangulation and member checking. The findings reveal that most universities lack a specific research roadmap on waste management, resulting in limited contributions to policy formulation. Although research and publication training has been implemented, it has not yet focused on environmental policy advocacy. Regression results indicate that policy formulation has a positive and significant effect on multi-actor collaboration (p < 0.05), while communication and coordination show positive but insignificant effects. The model explains 62.05% of the variance in collaboration outcomes. This study concludes that clear, directed, and inclusive policy formulation plays a more critical role than communication alone and recommends strengthening university engagement in evidence-based policymaking